1996
DOI: 10.1074/jbc.271.18.10640
|View full text |Cite
|
Sign up to set email alerts
|

The Conformational Properties of the Highly Selective Cannabinoid Receptor Ligand CP-55,940

Abstract: During a search for novel drugs possessing analgesic properties but devoid of the psychotropic effects of marijuana, a group of molecules designated as nonclassical cannabinoids was synthesized by Pfizer. Of these nonclassical cannabinoids CP-55,940 has received the most attention principally because it was used as the high affinity radioligand during the discovery and characterization of the G-protein-coupled cannabinoid receptor. In an effort to obtain information on the stereoelectronic requirements at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 23 publications
6
62
0
Order By: Relevance
“…At the CB 1 WT binding site identified by modeling studies, CP55,940 is oriented with all three hydroxyls on the same face of the molecule. This orientation of the hydroxyls is consistent with the binding site model for CP55,940 proposed by Xie et al (1996) based upon NMR solution spectra. Each of these hydroxyls finds a hydrogen bonding interaction in the CB 1 WT R* bundle model.…”
Section: Discussionsupporting
confidence: 73%
“…At the CB 1 WT binding site identified by modeling studies, CP55,940 is oriented with all three hydroxyls on the same face of the molecule. This orientation of the hydroxyls is consistent with the binding site model for CP55,940 proposed by Xie et al (1996) based upon NMR solution spectra. Each of these hydroxyls finds a hydrogen bonding interaction in the CB 1 WT R* bundle model.…”
Section: Discussionsupporting
confidence: 73%
“…Based on substantial experimental evidence, it has been proposed that lipophilic ligands interact with their respective target proteins by first partitioning into the membrane bilayer where they assume a preferred location and orientation (5). We can thus postulate that the lipophilic anandamide resides predominantly within the membrane bilayer either following its release within a neural synapse or after its enzymatic synthesis within the cell membrane by membrane-bound enzymes (7).…”
Section: How Anandamide Reaches Its Active Site At the Cb1 Receptormentioning
confidence: 99%
“…Accumulated evidence indicates that many fatty acid-derived lipophilic neurotransmitters are synthesized, stored, and degraded and also exert their functions within the lipid membrane (1,2). Therefore, it has been suggested that the conformation, location, and orientation of the ligand in the membrane are critical in determining its ability to reach and interact productively with its site of action (3)(4)(5). Exploring the conformational and dynamic properties of these ligands in the membrane can lead to a better understanding of the molecular features involved in their interactions with the target proteins (6).…”
mentioning
confidence: 99%
“…This response is accompanied by an elevation in tissue anandamide content, indicating that it might be due to a net increase in anandamide formation rather than to extracellular release of preformed anandamide 27 by the role of an intramembranous amino-acid residue (lysine-192) in the binding of anandamide to CB 1 (REF. 39), as well as by the finding that certain cannabinoid agonists can approach the receptor by lateral membrane diffusion 40 . Nevertheless, it does not account for two pieces of evidence.…”
Section: Daniele Piomellimentioning
confidence: 99%